Right ventricular responses to CPAP therapy in obstructive sleep apnea: CMR analysis of the MOSAIC randomized trial. (19th February 2023) - Samaranayake, Chinthaka B.; Turnbull, Christopher; Neubauer, Stefan; Kylintireas, Ilias; Stradling, John; Craig, Sonya; McCabe, Colm
Abstract: Effects of continuous positive airway pressure (CPAP) on right ventricular (RV) function in patients with untreated mild‐to‐moderate obstructive sleep apnea (OSA) are unclear. In this exploratory analysis of cardiac magnetic resonance (CMR)‐derived indices of RV function in patients with minimally symptomatic OSA from the MOSAIC randomized control trial we found no effect of CPAP on RV CMR parameters. In those with lower RV ejection fraction and higher RV end‐diastolic volume (EDV) at baseline, CPAP treatment appeared to improve RV function with a significant reduction in both RV EDV and RV end‐systolic volume although between‐group effects were not observed. These data suggest potential merit in a larger randomized study of CPAP in patients with mild‐to‐moderate OSA and a greater breadth of RV dysfunction.